Estimativa da correção do coeficiente de retorno de esgoto sanitário em habitações com sistemas de aproveitamento de água pluvial: estudo de caso da cidade de Bauru (SP) - Leão, Cintia Loturco Pinheiro [UNESP] (2015)
Several studies have been conducted proposing water conservation techniques to minimize the treated water consumption. Among them stands out the rainwater utilization in activities that may dispense the potability. In Brazil, the pricing on the collection and treatment services of sewage, is generally performed based on the volume of treated water measured at the meter of the consumer unit. Therefore, this sewage disposal generated by rainwater utilization system is not accounted for sewage charging system on the cost of disposal and treatment. The use of this rainwater underestimates the volume of sewage generated. This paper proposes the application of the methodology for setting this return coefficient to estimate the volume of rainwater released in the sewage disposal system linked to the volume of treated water measured at the meter of each consumer unit. The sanitary bowl with box attached was adopted as an object of study. From the collection of roof areas sampling the city of Bauru (SP) determined the average area of the roof. Different simulations of determining roof areas, reservoir volumes and water consumption demands were made, in order to analyze the return coefficient setting behavior for the average area of roof per capita (m2.hab-1). The results showed that the city of Bauru (SP) features a roof area of approximately 139.91 = 3.12 m2 for homes, 5.58 m2.hab-1 for apartments and wa weighted average area of 132.18 m2 per household. With an average are per capita of 49,21 m2. It was found that in all per capita consumpetion ranges, for volume of 0.5 m3 reservoir/in habitant, the release of rainwater in the sewage disposal system was efficient with values less than 30% specific coverage areas 4-17 m2.hab-1 therefore concluded that discharges into sanitary bowl were not met fully by rainwater utilization system. In this way it was stated that not all use of water for unloading in sanitary bowl is transferred to the collection...